Vertical Specialization, International Task Fragmentation, and Convergence - Sugata Marjit; Reza Oladi (Center for Economic Studies and ifo Institute (CESifo), 2021)
In this paper, we construct an elaborate general equilibrium model with a continuum of production fragments for an intermediate good, then embed it in a growth model to address the effects of global production fragmentation, vertical specialization and trade on growth and inequality for a small developing country. Among other results, we show that a small developing economy grows faster than the rest of the world as a result of global fragmentation and trade in intermediates if it is skilled-labor scarce. We also address the effects of such trade opening on wage inequality.
Keywords: F10; 330; vertical specialization; trade; growth; inequality